Analisis Penerapan Withholding Tax System Pada Pajak Penghasilan Final Pasal 4 Ayat 2 Atas Usaha Jasa Konstruksi di PT. Aditata Bersama Aplikator : Analysis of the Implementation of the Withholding Tax System Under Article 4, Paragraph 2 of the Final Income Tax Law for Construction Services at PT. Aditata Bersama Aplikator - Andriyani, Desi; Riftiasari, Dinar (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This research is motivated by the importance of implementing Final Income Tax Article 4 Paragraph 2 for companies operating in Indonesia, specifically PT. Aditata Bersama Aplikator. The aim of this study is to analyze the implementation of tax withholding and payment at the company and identify the errors that occurred. The research method used is a qualitative approach with a case study, where data was collected through interviews with relevant parties and analysis of the company's tax documents. The results show that although the company has made efforts to implement the withholding tax system in accordance with the regulations, there are discrepancies in transaction classification, leading to errors in applying the tax rates and delays in reporting. These inaccuracies may result in fines and issues with tax authorities. The study suggests that the company improve its tax administration system, provide training to the tax team, and strengthen internal supervision to minimize errors in tax reporting and payment.